HUBUNGAN PENGETAHUAN, TINGKAT STRES DAN PERSONAL HYGIENE TERHADAP KEJADIAN FLOUR ALBUS (KEPUTIHAN) PADA REMAJA PUTRI DI SMK KESEHATAN ASY-SYIFA KOTA TANGERANG TAHUN 2022 - Hofifah Alawiyah; Jesy Fatimah (PT. Hasba Edukasi Mandiri, 2026)
Fluor Albus is the discharge of non-blood fluid from the vagina outside of normal conditions, with or without odour, and often accompanied by local itching. The causes of vaginal discharge can be physiological and influenced by certain hormones. This study aims to identify the relationship between knowledge, stress levels, and personal hygiene on the incidence of fluor albus among female students at Asy-Syifa Health Vocational School in Tangerang City. The research method applied is descriptive analytical with a cross-sectional design. The study population consisted of 168 female students, and the sampling technique used stratified random sampling with a sample size of 63 female students. The results showed a significant relationship between knowledge and the incidence of fluor albus, with a P value of 0.000, which is smaller than the alpha value (0.000 < 0.05). Similarly, there was a significant relationship between stress levels and fluor albus, with a P value of 0.001, which was also smaller than the alpha value (0.001 < 0.05). In addition, a significant relationship was also found between personal hygiene and fluor albus, with a P value of 0.000, which was smaller than the alpha value (0.000 < 0.05). The conclusion of this study is that there is a relationship between knowledge, stress levels, and personal hygiene and the incidence of fluor albus (vaginal discharge) among female adolescents at the Asy-Syifa Health Vocational School in Tangerang City in 2022.